Peningkatan Kualitas Produksi dan Keamanan Pemasaran Minuman Kesehatan Berbasis Bunga Telang pada Ibu PKK Kecamatan Rungkut Surabaya dalam mendukung SDGs-3 Good Health and Well Being: Improving the Quality of Production and Marketing of Telang Flower Based Health Drinks to PKK Women, Rungkut District, Surabaya in support of SDGs-3 Good Health and Well Being - Ekowati, Juni; Prawitasari, Neny; Ifadotunnikmah, Farida; Bastiana, Bastiana; Yuwono, Mochammad; Suzana, Suzana; Susanto, Julian Dwi; Ulvan, Angkasa Megistra; Hartono, Thalia Vanessa; Shihab, Fawaz; Afandi, Ryan; Setiawan, Albertus Aditya; Febrianti, Winanda Rizki (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
To support SDGs-3 to achieve conditions of good health and well-being amidst the conditions of society, support is needed for resilient community groups who are economically creative. The residents of Penjaringan Sari Village are among the village residents who have won Surabaya SMART City 2020. They are an alternative tourist village developing a productive economy by selling processed drinks based on Telang flowers. However, in this community group, many problems still require assistance. Efforts need to be made to solve the problems of PKK women's partners in the Penjaringansari sub-district to improve production quality, starting from preparing raw materials, selecting and using packaging correctly, and increasing the diversification of partners' processed products and product branding. This activity aims to provide community service from a team of lecturers from the Faculty of Pharmacy, Airlangga University, in collaboration with lecturers from the Faculty of Medicine, Nahdatul Ulama University, Surabaya. This activity is a tri dharma of higher education where the community can feel lecture materials, research results, and previous community service products as partners in supporting SDGs-3 Good Health and Well-being. The outcome is an increase in participants' understanding, indicated by an average post-test score of 75, with an increase of 26% compared to the pretest. Apart from that, there is an increase in skills in making syrup and Telang flower powder drinks.